Phosphonate‐Mediated Immobilization of Rhodium/Bipyridine Hydrogenation Catalysts. Issue 10 (25th January 2018) - Forato, Florian; Belhboub, Anouar; Monot, Julien; Petit, Marc; Benoit, Roland; Sarou‐Kanian, Vincent; Fayon, Franck; Jacquemin, Denis; Queffelec, Clémence; Bujoli, Bruno
Abstract: RhL2 complexes of phosphonate‐derivatized 2, 2′‐bipyridine (bpy) ligands L were immobilized on titanium oxide particles generated in situ. Depending on the structure of the bipy ligand—number of tethers (1 or 2) to which the phosphonate end groups are attached and their location on the 2, 2′‐bipyridine backbone (4, 4′‐, 5, 5′‐, or 6, 6′‐positions)—the resulting supported catalysts showed comparable chemoselectivity but different kinetics for the hydrogenation of 6‐methyl‐5‐hepten‐2‐one under hydrogen pressure. Characterization of the six supported catalysts suggested that the intrinsic geometry of each of the phosphonate‐derivatized 2, 2′‐bipyridines leads to supported catalysts with different microstructures and different arrangements of the RhL2 species at the surface of the solid, which thereby affect their reactivity. Abstract : Heterogenized catalysts : Immobilization of rhodium complexes of phosphonate‐derivatized 2, 2′‐bipyridines on titanium oxide/hydroxide particles generated in situ led to supported catalysts for olefin hydrogenation (see figure). Grafting of the phosphonate groups on the oxide matrix was probed by DFT studies, 31 P MAS NMR spectroscopy, and ToF‐SIMS. The structure of the bipyridine ligand was found to strongly influence the microstructure of the resulting supported catalysts, which in turn affected the reaction rate.